Analysis of active decoy deploymentagainst anti-radiation missiles - sastry Vijayalakshmi, E.; N.N. Sastry, Dr.; B.Prabhakar rao, Dr. (International Journal of Engineering and Technology, 2019)
Missile threats are the most dangerous ones and valuable platforms like ships and land based installation have become most vulnerable targets. To counter multiple or singular missile attacks, with radar terminal phase homing both hard kill in the form of anti missiles and soft kill in the form of decoys have been used with increasing success rate for protecting the vital installations and platforms. In this paper, active decoy deployment for most effective luring away of missiles from the installations and platforms is analyzed and discussed. Miss distance of the missiles from the vital targets is computed with various parametric studies and is analyzed. It is shown that maximum miss distance is obtained, when the active decoy is positioned around 1100 from the reference axis of the target platform. Optimum angular deployment positions for various J/S ratios have been analyzed and results presented.